The Effect of Orthodontic Therapy on Periodontal Health: A Review of the Literature - Samah Alfuriji; Nora Alhazmi; Nasir Alhamlan; Ali Al-Ehaideb; Moatazbellah Alruwaithi; Nasser Alkatheeri; Amrita Geevarghese (Hindawi Limited, 2014)
Objectives. This review aims to evaluate the effect of orthodontic therapy on periodontal health. Data. Original articles that reported on the effect of orthodontic therapy on periodontal health were included. The reference lists of potentially relevant review articles were also sought. Sources. A literature search was conducted using the databases, Medline, EMBASE, Cochrane Library, Web of Science, Google Scholar, and Scopus databases for relevant studies. The search was carried out by using a combined text and the MeSH search strategies: using the key words in different combinations: "periodontal disease," "orthodontics" and "root resorption." This was supplemented by hand-searching in peer-reviewed journals and cross-referenced with the articles accessed. Articles published only in English language were included. Letters to the Editor, historical reviews and unpublished articles were not sought. Conclusions. Within the limitations of the present literature review, it was observed that there is a very close inter-relationship between the periodontal health and the outcome of orthodontic therapy.